CFD simulations of the indoor climate of a low energy building in a sub-Arctic climate: an evaluationof different heating systems. - Risberg, Daniel; Vesterlund, Mattias; Westerlund, Lars; Dahl, Jan (Luleå tekniska universitet, Energivetenskap, 2013)
Computational Fluid Dynamics (CFD) simulations were used to study the indoor climate in a low energy building in northern Sweden. The building’s low heat requirements raise the prospect of using relatively simple and inexpensive heating systems to maintain an acceptable indoor environment, even in the face of extremely low outdoor temperatures. To explore the viability of this approach, the indoor temperature and air velocity distribution inside the building were studied assuming that it was fitted with one of four different heating systems: radiators, an underfloor heating system, a pellet stove, and an air/air heat pump. The radiators produced a relatively uniform horizontal temperature distribution throughout the house. The underfloor system provided an even more uniform temperature distribution. In contrast, the heat pump created a relatively uneven internal temperature distribution. Several locations for the pump were considered, all of which had significant drawbacks. The pellet stove produced a more even temperature distribution than the pump but not to the same extent as the underfloor system or the radiators. Overall, point source heating systems cost less to fit and operate over a given period of time but produce a less clement indoor environment than distributed heating systems. Godkänd; 2013; 20140305 (matves)